2002
DOI: 10.1051/0004-6361:20021094
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive optics observations of asteroid (216) Kleopatra

Abstract: Abstract. The large main-belt asteroid (216) Kleopatra has been for long suspected to be a binary object, mainly due to its large lightcurve amplitude. However, recent observations suggest that it is a single "bone-shaped" or bi-lobated body (Ostro et al. 2000;Tanga et al. 2001). We present results obtained from ground-based adaptive optics observations, and in agreement with the radar raw-observations, the images show two prominent lobes. Making use of the MISTRAL deconvolution technique, the restored images … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 15 publications
(24 reference statements)
0
17
0
Order By: Relevance
“…• , β = 23 • , which had been confirmed by Hestroffer et al (2002b) with the adaptive optics technique. Model shapes and scattering functions are mentioned in the following sections.…”
Section: Lightcurve Simulationsmentioning
confidence: 57%
See 4 more Smart Citations
“…• , β = 23 • , which had been confirmed by Hestroffer et al (2002b) with the adaptive optics technique. Model shapes and scattering functions are mentioned in the following sections.…”
Section: Lightcurve Simulationsmentioning
confidence: 57%
“…The two observations by the radar and interferometric techniques indicated that (216) Kleopatra had a shape with two components in contact, but Hestroffer et al (2002b) suggested that the two bodies could be separated by analyzing data from an adaptive optics system, ADONIS, installed on the 3.6 m ESO telescope, using the MISTRAL deconvolution technique. Binary model-Roche Binary Equal-sized binary asteroids in the size range of 100 km could be formed by catastrophic collisions (Farinella et al, 1982).…”
Section: Lightcurve Simulationsmentioning
confidence: 99%
See 3 more Smart Citations